Utilization of the Socialization Application of New Habits Adaptation Policies based on Android Information Technology in the Jabung Village Community, Laren District, Lamongan Regency - Anajeng Esri Edhi Mahanani; Teddy Prima Anggriawan; Eko Wahyudi; Zuhda Mila Fitriana; Alvian Dwiangga Wijaya (Future Science, 2021)
In terms of handling non-natural disasters, namely the COVID-19 pan-demic, many policies have been issued. The many types of policies that can be taken to prevent, and overcome the impact of the COVID-19 pandemic and its spread, must be properly socialized to the public. The preparation of an android application to socialize the adaptation policy of this new habit, to answer the problems that occurred in Jabung Village, Laren District, Lamongan Regency, namely the lack of public awareness which tends to lead to apathy towards the COVID-19 pandemic and policies that will be taken soon, namely the policy of adopting new habits. This policy must be understood as a normal life policy with the application of strict health protocols, it must be understood by all levels of society in the context of overcoming COVID-19 in Indonesia.